Resource-based view in strategic management of public organizations - a review of the literature = Podejście zasobowe w zarządzaniu strategicznym organizacją publiczną - przegląd literatury - Szymaniec-Mlicka, Karolina (Zielona Góra: Faculty of Economics and Management Press)
The resourced-based view has been widely used and appreciated in strategic management of private organizations. It is not, however, particularly popular in public management, although, as pointed out by the literature, it may be the solution to environmental turbulences that public organizations also have to face. This article focuses on presenting a review of to-date research relating to the use of resource-based view in the management of public organizations.
Keywords: organizacja publiczna; zarządzanie publiczne; podejście zasobowe; public organisation; public management; resource based view (RBV)